PREPARATION OF THE EDUCATIONAL ENVIRONMENT FOR AN INCLUSIVE PROCESS IN THE INSTITUTIONS OF GENERAL SECONDARY EDUCATION - Skrypnyk, Tetiana (Educological discourse, 2020)
This article is devoted to approaches to the targeted and consistent preparation of the educational environment for inclusive learning in educational institutions. The author reveals the limited and controversial nature of the concept of «inclusive educational environment» in Ukrainian regulatory and educational materials; the author presents international guidelines, according to which the educational environment acquires such characteristics as: free, stimulating, supportive, developing for all students. The author carefully analyses the content and structural components of the classroom management strategy (object spatial, organizational-semantic, socio-psychological), aimed at positive transformation of the educational environment for the success of each participant in the educational process. The author presents research on the implementation of the «Classroom Management» strategy in the educational process, in which seven educational institutions took part. The aim of the research was to carry out positive transformations in the educational environment as the basis for the implementation of effective inclusive education. According to expert assessments of the teaching staff, the changes achieved have significantly improved the start of inclusive education. In turn, the team of organizers and experts of this research noted the particular success of two schools, the teaching teams of which showed sincere interest in the proposed approach and joined the preparatory work not as consumers, but as real partners, with enthusiasm, creative proposals, a desire to transform the environment for the better and achieve greater success in student learning and development. The results obtained showed the effectiveness of the «Classroom Management» strategy, which positively transform the educational environment and contribute to the development of a competent inclusive process.